Kearifan Lokal Masyarakat Bangka Belitung dalam Cerita Rakyat “Batu Balai”: Kajian Pendidikan Karakter - Lasmi Hartati; Lili Liana; Muhammad Rozani (Universitas Muhammadiyah Surabaya, 2024)
There are various folk tales that contain local wisdom values. Folklore has many meanings in character formation. The aim of this research is to describe the benefits of folklore as a form of character formation. The method used in this research is descriptive qualitative. The research data sources were Batu Balai folklore documents, as well as interviews with informants which were then transcribed in narrative form. Interactive analysis was used to analyze the data, which was validated using triangulation and informant evaluation methods. Based on the research conducted, seven characters were found that emerged from the story. The characters found are independence, hard work, patience, commitment, mutual cooperation, honesty and politeness. The most dominant value of the seven values ​​is the value of hard work and mutual cooperation. Of course, this can be seen from the behavior or attitudes of the characters in the story. Especially the main character who tries to help his mother's economy. This needs to be implemented, because in the current era of digitalization, children are busy with their devices.